Quantitative Analysis of System Operating Margin With the High Penetration of Distributed Generators in Distribution Networks - Zhu, Ruijin; Dong, Yali; Zhao, Wentao; Gong, Xuejiao; Tang, Bo (Frontiers in Energy Research, 2022)
With the integration of distributed generators (DGs) and multiple types of loads, it is increasingly difficult to cope with the uncertainties of DG, which brings challenges to the secure operation of distribution networks (DN). In addition, the source and load at nodes cannot obtain the power balance locally, which may cause operational problems such as line power overload and node voltage violation. However, the methods for quantitatively analyzing the operating status of DN have not yet formed a unified standard. In which reason the concept of operating margin is proposed in this paper, to represent the distance from operating point to the boundary. In this paper, to generally evaluate the operating status of DN, the concept of node power margin is proposed firstly. Then the evaluation indexes including line power margin (LPM) and node voltage margin (NVM) are introduced. The quantitative calculation method for system operating margin (SOM) is further elaborated, which is supposed to be the evaluation indexes on system level. After that, the analysis process of evaluation methods for SOM are discussed. Finally, case studies are performed on the modified IEEE 33-node system to evaluate the operating margin of DN and verify the enhancement brought by energy storage system (ESS) and soft open point (SOP) through the flexible adjustment of power flow. The simulation results show that the distance between the DN and the security boundary is effectively quantified.